2021
DOI: 10.3390/biology10020167
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavages in the VEGF Family: Generating Diversity among Angiogenic VEGFs, Essential for the Activation of Lymphangiogenic VEGFs

Abstract: Specific proteolytic cleavages turn on, modify, or turn off the activity of vascular endothelial growth factors (VEGFs). Proteolysis is most prominent among the lymph­angiogenic VEGF-C and VEGF-D, which are synthesized as precursors that need to undergo enzymatic removal of their C- and N-terminal propeptides before they can activate their receptors. At least five different proteases mediate the activating cleavage of VEGF-C: plasmin, ADAMTS3, prostate-specific antigen, cathepsin D, and thrombin. All of these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 154 publications
0
41
0
Order By: Relevance
“…The VEGF family is a key mediator of angiogenesis (7). Blocking VEGFA is used to treat tumors (20). In one study, patients benefited from Ramncirumab, a monoclonal antibody that binds to VEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF family is a key mediator of angiogenesis (7). Blocking VEGFA is used to treat tumors (20). In one study, patients benefited from Ramncirumab, a monoclonal antibody that binds to VEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Muramatsu et al [ 30 ] have reported that the angiogenesis in an Ang I-infused sponge-implanted model was markedly suppressed by treatment with a chymase-specific inhibitor, and this suppression was achieved through the inhibitory effects on the chymase-Ang II-VEGF-dependent pathway, indicating that chymase-generated Ang II participates in the neovascularization process through the increase in VEGF expression. As is well known, both angiogenesis and lymphangiogenesis in malignant tumors is accelerated by VEGF, and they may increase the frequency of blood and lymphatic metastases [ 31 ]. On the other hand, angiogenesis could also increase nutrient supply and contribute to tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing liberates a variety of VEGFA species which differ in their capacity to bind VEGFRs, co-receptors and ECM components [ 37 , 43 ]. In contrast, VEGFC and VEGFD comprise a central VEGF homology domain (VHD), flanked by N- and C-terminal pro-peptides that are proteolytically cleaved to generate mature growth factors with maximal affinity for binding to and activating VEGFR3 [ 50 ]. Proteases established to mediate VEGFC cleavage include ADAMTS3 [ 25 ], Adamts14 [ 51 ] (in zebrafish), plasmin [ 52 ], thrombin [ 53 ], kallikrein-related peptidase 3 (KLK3) [ 54 ] and cathepsin D [ 54 ].…”
Section: The Vascular Endothelial Growth Factor Familymentioning
confidence: 99%